CCTF: congestion control protocol based on trustworthiness of nodes in Wireless Sensor Networks using fuzzy logic. (29th July 2011) - Zarei, Mani; Rahmani, Amir Masoud; Farazkish, Razieh
In Wireless Sensor Networks (WSNs) the existence of malicious nodes is a serious challenge. Malicious nodes increase the traffic by sending distrusted messages. In this paper, we present CCTF: a congestion control protocol based on trustworthiness of nodes in WSNs using fuzzy logic. Through the use of CCTF, each node reduces malfunctioning neighbour(s) effects via dropping valueless packets and increases the buffer capacity; consequently, the chance of network congestion reduces. Simulation results show that when 16% of all nodes are malicious, CCTF increases the packet delivery ratio up to 40% meanwhile it reduces the packet drop ratio nearly 27.5%.